Determinants of Homeownership Intention: The Moderating Role of Government Support - Mulyadi, Mulyadi (UNIMAS, 2025)
The housing situation in Indonesia presents significant challenges, with homeownership becoming increasingly difficult despite its economic importance. While prior research attributes declining homeownership mainly to economic factors, broader determinants remain underexplored. This study investigates the determinants of homeownership intentions in Central Java, integrating economic, socio-psychological, cultural, and governmental factors. Rooted in Rational Choice Theory, the Theory of Reasoned Action, the Theory of Planned Behavior, and the Theory of Housing Adjustment, the study utilizes a multistage sampling method. This approach includes cluster sampling to group regions, quota sampling to establish sample quotas, and purposive sampling for selecting respondents. Data were collected from 420 participants in districts with low homeownership rates. Findings reveal those economic factors such as financial risk perception and household debt significantly influence homeownership intentions. Socio-psychological variables, including attitudes, subjective norms, and perceived behavioral control, also play critical roles. Furthermore, government support moderates these relationships, exerting varying impacts. The study underscores the need for inclusive housing policies that enhance financial literacy, empower communities, and address cultural sensitivities.